Предмет: Математика, автор: Ильнара

(4/(a^3-2a^2)+(a+2)/a^2):((a+2)/(a-2)-(a-2)/(a+2)-16/(4-a^2))

 

ответ долден быть 1/8

Ответы

Автор ответа: ATLAS
0

(4/(a^3-2a^2)+(a+2)/a^2):((a+2)/(a-2)-(a-2)/(a+2)-16/(4-a^2))=

((4/(a^2(а-2))+(а+2))/((а^2)) : (((a+2)^2-(a-2)^2+16))/(a-2)(a+2))=

(4+(a+2)(a-2))/(a^2(a-2)): ((a^2+4a+4-a^2+4a-4+16)/(a-2)(a+2))=

(4+a-4)(a-2)(a+2)/(a^2(a-2)(8a+16))=

a(a+2)/(a^2*8*(a+2))=

=1/(8a)

 

Автор ответа: саскеучиха
0

4+a-4)(a-2)(a+2)/(a^2(a-2)(8a+16))=

a(a+2)/(a^2*8*(a+2))=

=1/(8a)

Похожие вопросы
Предмет: Математика, автор: NASTYA2338484